2004
DOI: 10.1248/bpb.27.1147
|View full text |Cite
|
Sign up to set email alerts
|

Lignans from the Bark of Machilus thunbergii and Their DNA Topoisomerases I and II Inhibition and Cytotoxicity

Abstract: DNA topoisomerases are enzymes involved in the relaxation of DNA during a number of critical cellular processes, including replication, recombination and transcription by transiently breaking one or two strands of DNA, passing a single-or double-stranded DNA through the break, and finally resealing the breaking.1-3) Currently, only a camptothecin (CPT) family of compounds as DNA topoisomerase I-directed drugs has been introduced into the clinic to date, 4,5) though many topoisomerase II-directed drugs have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…5q-v), it could be possible that this extract (UNMC9EA) which induced similar DSBs acts also on microtubules or causes topoisomerase II inhibition in A549 cells. Many secondary metabolites isolated from plants are found to be topoisomerase II inhibitors including terpenoids, lignans, triterpenes and anthracenone (Lansiaux et al, 2001;Mizushina et al, 2003;Li et al, 2004;Wada and Tanaka, 2006). However, if UNMC9EA-induced cell death was the result of (a-f) Untreated cell lines; (g-l) Cell lines treated with 0.1 g/ml of UNMC9EA; (m-p) Cell lines treated with 0.1 g/ml UNMC9H; and (q-v) Cell lines treated with 10 g/ml of Vinblastine.…”
Section: Discussionmentioning
confidence: 99%
“…5q-v), it could be possible that this extract (UNMC9EA) which induced similar DSBs acts also on microtubules or causes topoisomerase II inhibition in A549 cells. Many secondary metabolites isolated from plants are found to be topoisomerase II inhibitors including terpenoids, lignans, triterpenes and anthracenone (Lansiaux et al, 2001;Mizushina et al, 2003;Li et al, 2004;Wada and Tanaka, 2006). However, if UNMC9EA-induced cell death was the result of (a-f) Untreated cell lines; (g-l) Cell lines treated with 0.1 g/ml of UNMC9EA; (m-p) Cell lines treated with 0.1 g/ml UNMC9H; and (q-v) Cell lines treated with 10 g/ml of Vinblastine.…”
Section: Discussionmentioning
confidence: 99%
“…The observed bone anabolic activity occurred in a dose-dependent manner. Other activities for machilin A include inhibition of proliferation of blood lymphocytes, human leukemia HL-60 cells, and topoisomerase I and II inhibition, suggesting potential anticancer properties (Hirano et al 1991, Hirano et al 1994, Li et al 2004). Follow-up studies and proper clinical evaluation of these properties remain uninvestigated.…”
Section: Pharmacological Evaluation Of Pure Nutmeg Compoundsmentioning
confidence: 99%
“…Previously, we reported that meso-dihydroguaiaretic (MDGA) inhibits DNA topoisomerase I and II (Li et al, 2004). Other groups have reported that MDGA inhibits the expression of matrix metalloproteinase (MMP)-2, 9 in cultured human keratinocytes (Moon et al, 2005), downregulated TGFb-1 gene expression in activated hepatic stellate cells (Park et al, 2005), protected neuronal cells from staurosporine-induced apoptosis (Ma et al, 2006), and inhibited MMP-1 in primary human fibroblasts (Moon et al, 2006).…”
Section: Resultsmentioning
confidence: 99%